Slope fracture parameter in-situ test system and method based on resistivity method

Through the in-situ testing system for slope fracture parameters based on resistivity method, the high-density resistance method host and conductive hydrogel are used to solve the complexity and destructive problems of crack detection within soil slopes, and the rapid and accurate measurement of fracture parameters and the improvement of slope stability are achieved.

CN119688790AActive Publication Date: 2025-03-25CHANGSHA UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411880424.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-25
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

The prior art has problems such as complex operation, high cost, destructiveness and environmental factors when detecting cracks inside soil slopes.

Method used

A slope crack parameter in-situ testing system based on the resistivity method is adopted, which includes a high-density resistance method host installed on the surface, an electrical energy conversion device, a multi-electrode conversion device and a conductive hydrogel. By injecting conductive hydrogel and using the high-density resistance method to collect resistivity data, perform two-dimensional inversion calculations, and obtain the depth and parameters of the cracks.

Benefits of technology

It realizes rapid and accurate measurement of slope surface and internal cracks, with high accuracy, simplified operation and wide application range, can quickly complete the test work in a variety of environments, and reinforce the crack area through conductive hydrogel to inhibit further expansion of the cracks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119688790A_ABST
    Figure CN119688790A_ABST
Patent Text Reader

Abstract

The invention provides a side slope fracture parameter in-situ test system and method based on a resistivity method, and the specific process of the test method is as follows: firstly, obtaining side slope geological exploration data and side slope design parameters, determining the measuring line length, the electrode bar spacing and the isolation coefficient of three main fractures, and calculating the detection depth; conductive hydrogel is injected into the slope crack, a measuring line is arranged, and an electrode bar is installed; acquiring an underground longitudinal section resistivity distribution diagram, and determining the fracture depth; inserting an electrode bar into the slope body to the maximum crack depth, fixing the electrode, and measuring slope surface crack parameters; moving the electrode downwards to different layers, and measuring fracture parameters of each layer; and importing the fracture parameters and depth into a computer for modeling to determine the volume fracture rate of the whole slope. According to the method, parameters of cracks on the surface and in the slope can be rapidly and accurately measured, the method has the advantages of being environmentally friendly and saving energy, and meanwhile the injected hydrogel can play a reinforcing role in inhibiting development of the cracks.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of geotechnical engineering, and in particular relates to an in-situ testing system and method for slope crack parameters based on a resistivity method. Background Art

[0002] With the continuous development of public infrastructure such as railways, highways, hydropower, waterways and ports, many artificial soil slopes are inevitably generated. These soil slopes are prone to shrinkage cracks under the action of atmospheric dry-wet cycles. The formation of cracks will directly reduce the shear strength of the soil. On the other hand, it can serve as a dominant seepage channel to accelerate rainwater infiltration during rainfall, which will have a serious impact on the stability of the slope and eventually cause shallow instability disasters such as slope collapse and landslide. Therefore, it is of great significance to measure the crack parameters of the slope on site.

[0003] The existing mature technology can easily obtain the crack parameters on the surface of soil slopes, but it is not enough to reflect the crack conditions inside the soil. The existing crack test methods can be divided into two categories: indoor test methods and outdoor test methods. The indoor test methods mainly include CT test method and grouting method. Although the CT test method can realize real-time, continuous, non-destructive detection of the tested soil samples with high resolution, its operation is complicated, the cost is high, the test process is harmful to the human body, and special equipment is required, which limits its application in slope crack parameter testing. The grouting method is to inject flowing materials (such as resin, gypsum, paraffin, etc.) into the cracks, and then dig up the soil after the flowing materials solidify. The crack morphology and parameters are obtained by directly measuring the parameters of the solidified materials. Although this method can better test the various parameters of the cracks, it will cause irreversible damage to the slope soil. The outdoor test methods mainly include drilling method, digital photography crack test method and ultrasonic method. The drilling method will change the original structure of the slope cracks during drilling, causing errors in the crack parameters, and will destroy the integrity of the slope during construction. The digital photography crack test method is mainly used for the determination of surface crack parameters, and its accuracy is greatly affected by instruments and equipment, lighting environment interference and human factors, especially when there is plant coverage on the slope surface. It is more difficult to apply. The ultrasonic method is mostly used for homogeneous soil. Soil with more impurities can easily lead to discrete changes in the speed of sound waves, resulting in distortion of the crack test results. Summary of the invention

[0004] The purpose of the embodiments of the present invention is to provide a system and method for in-situ testing of slope crack parameters based on the resistivity method, so as to overcome the limitations of the prior art in the detection of internal cracks in soil slopes, such as complex operation, high cost, destructiveness, and great influence of environmental factors, and to provide an efficient and non-destructive in-situ measurement solution for crack parameters.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is an in-situ test system for slope crack parameters based on the resistivity method, comprising a high-density resistance method host arranged on the surface, one end of the high-density resistance method host is connected to an electric energy conversion device through a cable, and the other end is connected to a multi-channel electrode conversion device; the other end of the electric energy conversion device is connected to a small wind turbine generator set through a cable; the multi-channel electrode conversion device is connected to an electrode rod through a cable and a probe;

[0006] An electrode rod, the electrode rod is inserted into the slope to be measured, and the electrode rod includes a plurality of probes;

[0007] Electrodes, used for measuring voltage, wherein the electrodes are fixed on different probes to achieve measurement at different depths;

[0008] The probe is specifically a movable conductive probe, which is used to adjust the measurement depth and realize conduction between the electrode and the multi-channel electrode conversion device.

[0009] An in-situ test method for slope crack parameters based on resistivity method comprises the following steps:

[0010] S1. Select three most developed cracks on the slope through field survey and inject conductive hydrogel into these cracks;

[0011] S2, determine the total length L of the three cracks measured by S1, the electrode rod spacing X, the isolation coefficient n and calculate the detection depth D = nX;

[0012] S3, according to the data determined in S2, the electrode rods are arranged at a spacing of X, and the electrode rods are connected by cables to construct an electrode network in a vertical direction, and the electrode network is then connected in series with the cables via a multi-channel electrode conversion device to connect to a high-density resistance method host, so that the high-density resistance method host can collect data of each electrode rod;

[0013] The electrode mesh is placed at the midpoint of the width direction on the horizontal plane of the crack;

[0014] S4. Determine the electrode rods used for power supply and measurement during the measurement process, use the high-density resistance method host to convert the voltage data collected by each electrode rod into resistivity data, determine the apparent resistivity at each measuring point, and perform two-dimensional inversion calculation on the apparent resistivity to obtain the high-density resistance method apparent resistivity cross-sectional distribution map of the three cracks along the depth direction, and finally determine the depths h1, h2, and h3 of the three cracks, and use the maximum value of the three as the deepest crack depth on the slope to be measured, recorded as h max ;

[0015] S5. Inject conductive hydrogel into all cracks on the slope until it is flush with the slope surface. Divide the slope surface into multiple rectangles according to 1 / 10 to 1 / 5 of the length and width of the slope. Insert electrode rods at the corners of the rectangles and redistribute the electrode rods. The insertion depth is h. max ; Move all electrodes on the electrode rods to the probe at the same height as the slope surface and fix them to detect and measure the crack parameters on the slope surface;

[0016] S6. Measure the crack parameters of each layer and the volume crack ratio of the slope.

[0017] Furthermore, the electrode rod spacing X in S2 is between 1 / 10 and 1 / 15L.

[0018] Furthermore, the determination process of the apparent resistivity cross-section distribution map by the S4 high-density resistance method is as follows:

[0019] S401, setting the distance between the electrode rods to X, selecting the first and fourth electrode rods as power supply electrode rods A and B, and the second and third electrode rods as measurement electrode rods M and N for measurement; marking the underground resistivity characteristic at the midpoint between the two points MN and the depth X as point a;

[0020] S402, keep the distance between the electrode rods at X, select the second and fifth electrode rods as power supply electrode rods A and B, and the third and fourth electrode rods as measurement electrode rods M and N for measurement; mark the underground resistivity characteristic at the midpoint between the two points MN and the depth X as point b; repeat the process of S401 to S402 until the measurement of all the measurement points in the row of ab connecting line is completed;

[0021] S403, set the spacing between the electrode rods to 2X, select the first and seventh electrode rods as power supply electrode rods A and B, and the third and fifth electrode rods as measurement electrode rods M and N for measurement; mark the underground resistivity characteristic at the midpoint between the two points MN and the depth of 2X as point c; repeat the process of S403 until the measurement of all measurement points in the row of point c is completed;

[0022] S404, setting the spacing between the electrode rods to 3X and 4X, respectively, and performing measurements in the manner of S403, processing the measured data through a high-density resistance method host, and modeling them as an apparent resistivity diagram of the cross section.

[0023] Furthermore, the S5 process of detecting crack parameters of the slope surface section is specifically as follows: the electrode is moved to the probe located on the slope surface position on the electrode rod, and all cables connected to the electrode rod are connected to the multi-channel electrode conversion device; after measuring each rectangular test area, the data is processed by the high-density resistance method host to determine the apparent resistivity cross-sectional diagram of the slope surface section, and the number of cracks in the slope surface section, the length, width and area of ​​each crack and the specific position of the crack on the section are determined by the output result of the host, and then the slope surface crack rate is determined.

[0024] Furthermore, the slope surface crack rate is specifically determined by:

[0025]

[0026] Where: s is the slope crack rate, A i is the crack area in the i-th test area, j is the number of test areas, and A is the area of ​​the entire test area.

[0027] Furthermore, in S5, four electrode rods are arranged as a group to form a rectangular test area, wherein the current input ends are electrode rods A and B; and the measuring electrode rods are M and N.

[0028] Furthermore, the specific process of S6 is as follows: the electrode rod is evenly divided into m sections, the length of each section is recorded as x, probes are set at both ends of each section, the electrode is fixed on the probe at a distance x from the slope surface, and the cable is connected to the multi-channel electrode conversion device to start measurement; when the measurement of the depth of the slope surface is x layers, the electrode is moved down to the next probe and measured again until the depth is measured to h max obtain the crack parameters at the section with a depth that is an integer multiple of x, establish a three-dimensional spatial model with the crack parameters, and determine the volume crack rate of the entire slope based on the three-dimensional spatial model.

[0029] Furthermore, the method for determining the volume crack rate is specifically as follows:

[0030]

[0031] Where: v is the volume crack ratio, V i is the volume of the i-th crack, k is the number of cracks, A is the area of ​​the entire test area, and H is the test depth.

[0032] Furthermore, the specific components of the hydrogel include: 10 to 12 parts by mass of agarose powder, 0.5 to 1.5 parts by mass of carbon nanotubes, and 18 to 20 parts by mass of sodium chloride;

[0033] The hydrogel is specifically prepared by the following method: firstly, sodium chloride powder is dissolved in 90-110 parts by weight of deionized water to prepare a sodium chloride solution, then agarose powder and carbon nanotubes are mixed and stirred to obtain a mixed powder, and after stirring evenly, the prepared sodium chloride solution is slowly added to the mixed powder.

[0034] Compared with the prior art, the beneficial effects of the present invention include the following points:

[0035] 1. The method proposed in the present invention can realize rapid and accurate measurement of cracks on the surface and inside of the slope (including but not limited to key parameters such as crack length, width, area, depth and crack ratio). The present invention not only has the characteristics of high precision, but also has extremely strong ease of operation and a wide range of applications, and can quickly complete the test work in a variety of environments.

[0036] 2. In order to improve the efficiency of crack identification and enhance the stability of slopes, the present invention introduces a new type of ion conductive hydrogel material. This material has high strength, high fluidity and excellent conductivity (resistivity between 10 -2 ~10 -1 Ω·m), after being injected into the slope cracks, it can form a significant resistivity contrast with the surrounding medium, thereby facilitating the rapid location of the crack structure. At the same time, due to its unique physical and chemical properties, the hydrogel used in the present invention can also effectively reinforce the crack area and inhibit the further expansion of the crack, playing a dual role.

[0037] 3. Considering the importance of environmental protection, the present invention uses the airflow generated by passing vehicles on the highway to drive the power generation equipment, thereby obtaining stable and continuous electric energy. This self-sufficient power generation mechanism significantly reduces the demand for external energy and emits almost no pollutants during operation.

[0038] In summary, the new technology provided by the present invention overcomes many limitations of traditional methods and provides a new solution for the accurate detection of internal cracks in soil slopes by combining advanced material science and renewable energy technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0040] Figure 1 is a flow chart of the testing method of this embodiment;

[0041] Figure 2 is a cross-sectional view of the crack depth test of this embodiment;

[0042] Figure 3 is a top view of the crack depth test of this embodiment;

[0043] Figure 4 is an underground cross-section diagram of the test method of this embodiment;

[0044] Figure 5 is an underground top view of the test method of this embodiment;

[0045] Figure 6 This is the distribution diagram of electrodes on the same layer in this embodiment;

[0046] Figure 7 is a cross-sectional diagram of apparent resistivity of crack depth measured by high-density resistance method in this embodiment;

[0047] Figure 8 is a cross-sectional diagram of apparent resistivity of the slope surface section tested in this embodiment;

[0048] Fig. 9 This embodiment imports the data of cross-section measurement into the three-dimensional modeling software to model the fracture morphology diagram;

[0049] In the figure, 1. electrode rod; 2. electrode; 3. cable; 4. crack after conductive gel is injected; 5. multi-channel electrode conversion device; 6. high-density resistance method host; 7. electric energy conversion device; 8. wind turbine generator set. DETAILED DESCRIPTION

[0050] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0051] like Figure 1 This embodiment provides an in-situ test method for slope crack parameters based on the resistivity method, and the specific process is as follows:

[0052] S1. Conduct on-site surveys and select three most developed cracks on the slope, and inject highly conductive hydrogel into these cracks. This process not only enables the hydrogel to form a closed electrical circuit with the surrounding soil, but also significantly increases the resistivity difference between the cracks and the surrounding soil, making it easier to accurately identify and analyze the crack area.

[0053] S2. Determine the total length L of the survey line of the three most developed fractures obtained from the field survey, the spacing X between the electrode rods 1, and the isolation coefficient n, and calculate the detection depth D = nX.

[0054] In this embodiment, in order to ensure the balance between accuracy and workload, the spacing of the electrode rods 1 is selected between 1 / 10 and 1 / 15L; the isolation coefficient n needs to be adjusted according to the apparent resistivity cross-section diagram: n = p sum -(p a -1), p sum is the number of connected electrode rods 1; p a is the number of electrode rods in the device. Since the Wenner device is used, p a It is taken as 4 to ensure that the detection depth is greater than or equal to the depth of the crack 4 after the conductive gel is injected, so as to ensure that the crack depth can be detected.

[0055] In some possible implementations, in order to ensure the accuracy of modeling measurement, when considering the length of the measuring line, the total measuring line length L is equal to the actual length of the fracture 4 after the conductive gel is injected plus 2 to 3 times the electrode rod spacing X.

[0056] S3, such as Figure 2 , Figure 3 , prepare corresponding electrode rods 1 in the crack area. The number of electrode rods 1 is determined according to the length of the measuring line and the electrode rod spacing X. They are arranged according to the electrode rod spacing X, and each electrode rod 1 is connected by a cable line 3 to form an electrode network in the vertical direction, and the electrode network is placed at the midpoint of the width direction on the horizontal plane of the crack; then, a multi-channel electrode conversion device 5 is connected in series with the cable line 3 and connected to the high-density resistance method host 6, so that the high-density resistance method host 6 can collect the data measured by each electrode rod 1.

[0057] S4. Obtain the resistivity distribution map of the underground longitudinal section and determine the crack depth

[0058] The high-density resistance method host 6 converts the voltage data measured by the electrode rod 1 into resistivity data, determines the apparent resistivity at each measuring point, and performs a two-dimensional inversion calculation on the apparent resistivity to obtain the high-density resistance method apparent resistivity cross-sectional distribution diagram of the three cracks along the depth direction (such as Figure 7 ), and finally determine the depths of the three cracks h1, h2, and h3, and take the maximum value of the three as the deepest crack depth on the slope to be tested, recorded as h max .

[0059] In some specific implementations, the high-density resistance method host 6 analyzes and processes the data collected by the electrode rod 1 and performs inversion imaging to obtain an apparent resistivity cross-section diagram of the test section (such as Figure 7). The apparent resistivity distribution map can clearly show the location of the cracks in the test section, so that the depth of each crack can be determined. The test process requires measuring each of the three cracks once, and the depths of the three cracks are h1, h2, and h3. The specific process is as follows:

[0060] like Figure 7 This embodiment first determines the power supply electrode rods (A and B) and the measuring electrode rods (M and N) involved in the measurement process, adjusts the positions of these electrode rods 1, and records the resistivity data at different positions, thereby constructing an image of the underground structure.

[0061] S401, first determine the electrode rod spacing X, and arrange the electrode rods 1 on the ground according to the spacing X. Electrode rods A and B are power supply electrode rods used to inject current into the ground; electrode rods M and N are measuring electrode rods used to measure the voltage difference generated by the current.

[0062] S402, set the isolation coefficient to n=1, that is, the actual distance between the electrode rods 1 is equal to the basic spacing X. At this time, select the first electrode rod as A, the second as M, the third as N, and the fourth as B (such as Figure 7 The measurement result represents the underground resistivity characteristics at the midpoint between points MN and a depth of about nX, marked as point a.

[0063] S403, keeping n unchanged, the next group of electrode rods 1 are used as new A, M, N, and B electrode rods in turn, that is, the second electrode rod is set as the new A electrode rod, and the third to fifth electrode rods are respectively M, N, and B electrode rods, to obtain the data of point b. Repeat this process until all measurement points in rows a and b are completed.

[0064] S404. After completing a round of measurement, increase the isolation factor to n=2, which means that the spacing between the electrode rods used now becomes twice as large as before (2X). Select the first electrode rod as A, skip one electrode rod and select the third electrode as M, then select the fifth electrode as N, and finally the seventh electrode as B. Perform measurement under this configuration and record the result at point c. Similarly, continue along this pattern to form a sequence of measurement points in rows c.

[0065] S405, continue to increase the isolation factor n to n = 4. The final test result is an inverted trapezoid. The measured data is processed by the high-density resistance method host 6 and imported into the computer modeling to obtain the apparent resistivity map of the entire trapezoidal section. Figure 7 The depth of the crack can be read off.

[0066] S5. Insert electrode rod 1 into the slope to the maximum depth of the three cracks to establish an in-situ test system for slope crack parameters. Move the electrodes 2 on all electrode rods 1 to the same height as the slope surface and fix them. Measure the slope surface crack parameters: Inject conductive hydrogel into all cracks on the slope surface until they are flush with the slope surface. Divide the slope surface into several rectangles of equal size according to 1 / 10 to 1 / 5 of the length and width of the slope. Insert electrode rod 1 at the corner point of the rectangle. The insertion depth is h. max The electrode 2 on the electrode rod 1 is moved to the probe at the same height as the slope surface and fixed thereon. All cables 3 connected to the electrode rods are connected to the multi-channel electrode conversion device 5. After power is turned on, the apparent resistivity cross-section of the test area composed of each of the four adjacent electrode rods 1 can be measured. Combining the test results of all the test areas, the apparent resistivity cross-section of the slope surface section can be finally obtained. The output result of the host can be used to obtain the number of cracks in the slope surface section, the length, width and area of ​​each crack, and the specific position of the crack on the section.

[0067] In some specific embodiments, the test system electrode rods 1 established in S5 are distributed as follows: Figure 5 , Figure 6 , including electrodes 2 arranged underground, an electric energy conversion device 7 arranged on the surface for power supply, a high-density resistance method host 6, and a multi-channel electrode conversion device 5. Specifically, a plurality of electrode rods 1 are inserted into the slope to be measured, and a movable electrode 2 is arranged on the electrode rod 1. The electrode rod 1 is also provided with a plurality of probes, which are specifically movable conductive probes, for adjusting the measurement depth and realizing conduction between the electrode 2 and the multi-channel electrode conversion device 5.

[0068] In some possible implementations, four electrode rods 1 are set as a group, electrode rods A and B are current input and output ends, electrode rods M and N are voltage measurement electrode rods, and by moving and fixing the electrode 2 on the electrode rod 1, the fracture parameters at different depth sections can be measured.

[0069] In some specific embodiments, the high-density resistance method host 6 is also connected to a multi-channel power conversion device 7, which is used to power the system, specifically to convert the input electrical energy into the form of electrical energy required for the high-density resistance method. The electrical energy of the power conversion device 7 comes from a small generator set connected to it.

[0070] In some specific embodiments, the function of the multi-channel electrode conversion device 5 is to realize the automatic selection and switching of multiple electrodes. The multi-channel electrode conversion device 5 is connected to the electrode rod 1 through the cable 3 to ensure that the high-density resistivity method host can accurately identify and record the resistivity data from a specific layer. The multi-channel electrode conversion device 5 ensures the realization of subsequent data processing, calculation and imaging analysis.

[0071] In this embodiment, the high-density resistance method host 6 adopts the UltraMarker A4 time-frequency high-density electrical method instrument independently developed by Guoke (Chongqing) Instrument Co., Ltd., and different models can be selected according to needs. As long as it can complete the current injection into the electrode 2, measure the voltage drop generated by the current in the electrode array, multi-electrode switching and control, power management and have multiple communication interfaces, it is within the scope of disclosure of this embodiment. The electric energy used in the test process is provided by a portable small wind turbine generator set 8 installed on the roadside, and the high-speed driving of passing vehicles drives the wind turbine blades to rotate to generate electric energy.

[0072] In some specific embodiments, the crack parameters include crack length, width and crack area, and the position of the crack on the cross section.

[0073] In this embodiment, the multi-channel electrode conversion device 5 is connected to the electrode rod 1 , and conduction with the electrode 2 is achieved through a movable probe provided on the electrode rod 1 .

[0074] S6. Measure the crack parameters of each layer and the volume crack ratio of the slope;

[0075] h max Divide into m sections on average, each section is x long, and set probes at the end points of each section. After the slope surface crack parameter test is completed, electrode 2 is moved down x each time and fixed to the probe at that location, and then the power is turned on for measurement. Finally, the crack length, width, area and other parameters at the section with a depth of an integer multiple of x can be measured. The crack parameters and depth are imported into the computer, and the three-dimensional spatial morphology of the crack is determined by the modeling software to obtain the volume crack rate of the measured slope.

[0076] In some possible implementations, the modeling software uses 3D Studio Max, and the modeling results are as follows: Fig. 9 shown.

[0077] In some possible embodiments, the hydrogel is specifically a highly conductive hydrogel, which uses agarose gel as a carrier and is embedded with highly conductive carbon nanotubes (CNTs) to enhance electrical properties. The specific formula of the hydrogel described in this embodiment includes: the mass proportion of agarose powder is 10-12 parts, the mass proportion of carbon nanotubes is 0.5-1.5 parts, and the mass proportion of sodium chloride (NaCl) powder is 18-20 parts. The preparation process is specifically to first dissolve the sodium chloride powder in 90 to 110 parts by mass of deionized water to prepare a NaCl solution; then place the agarose powder and carbon nanotubes in an efficient mixing device and stir them thoroughly to form a uniform solid mixture; finally, slowly add the NaCl solution to the above solid mixture while continuing to stir until a uniformly dispersed agarose hydrogel is obtained.

[0078] The experimental results show that the hydrogel prepared in this embodiment has an 80%-90% improvement in electrical conductivity compared to untreated agarose gel. In addition, when the hydrogel is applied to the soil surface and dried, the tensile strength of the soil can be significantly improved by 25%-40%. This improvement is mainly attributed to the physical entanglement between the hydrogel and the soil particles and the additional mechanical support provided by the carbon nanotubes, thereby enhancing the overall bonding and structural stability of the soil.

[0079] After the hydrogel is injected into the cracks of the soil body in this embodiment, due to the excellent fluidity and good extensibility of the hydrogel, the cracks can be effectively filled and the bonding of the soil bodies on both sides can be promoted. The tensile strength of the treated soil body is not only significantly improved, but also the presence of the hydrogel prevents the further expansion of the cracks, enhancing the overall stability and durability of the soil body. The mechanism of action of the hydrogel in the cracks is reflected in three aspects: first, enhancing the bonding force. The agarose component in the hydrogel forms a physical entanglement with the soil particles, and the carbon nanotubes provide additional mechanical support, increasing the bonding strength of the crack interface. Secondly, constructing a conductive network. The carbon nanotubes form a continuous conductive network in the hydrogel matrix, which not only improves the conductive properties of the material, but also may accelerate the curing process of the hydrogel by means of induction heating, further strengthening its bonding with the soil body. Finally, ductility and flexibility. The high ductility and flexibility of the hydrogel itself enable it to deform when subjected to external forces without breaking easily, thereby effectively buffering and dispersing stress and preventing the cracks from reappearing or expanding.

[0080] Example 1

[0081] S101. According to the geological survey report, summarize the geological survey data and slope design parameters of the measured soil slope, where the geological survey data includes soil physical and mechanical parameters. The representative area of ​​the slope to be measured is 10m long and wide. The on-site investigation found that the lengths of the three most strongly developed cracks are 1.2m, 1.0m and 0.9m respectively. According to the principle of high-density resistance method combined with the slope size and crack size, it is determined that the total length L of the measuring line is 2m, the electrode rod spacing X is 0.15m, the isolation coefficient n is 4, and the detection depth D = nX = 0.6m.

[0082] S102, Install the instrument

[0083] Inject high-fluidity and high-conductivity hydrogel into the cracks until the hydrogel is basically flush with the ground, and stop injecting to ensure that the conductivity at the cracks is different from the surrounding soil. Connect the power supply power conversion device 7, the high-density resistance method host 6 and the multi-channel electrode conversion device 5 with a cable 3. Install the electrode rod 1 on the ground at the midpoint of the crack width direction on the horizontal plane according to the electrode rod spacing of 0.15m. The depth of the electrode rod 1 into the soil shall not exceed one tenth of the electrode rod spacing of 0.15m, and connect the surface electrode rod 1 to the cable 3.

[0084] S103, Detection of crack depth

[0085] Turn on the power and use the high-density resistance method host 6 to collect the data collected by the electrode rod 1. After collection, the data is processed through the inversion software in the host. The processing steps are as follows: import data - check data reliability - eliminate negative values ​​- parameter setting - inversion processing - convergence detection - detail adjustment. According to the inverted apparent resistivity cross-section diagram and the difference between high resistivity (normal soil) and low resistivity (hydrogel in cracks), the crack depth h is judged to be 0.5m, 0.48m and 0.4m respectively, and the maximum value h=0.5m is taken as the maximum depth that cracks can develop in the test area. The apparent resistivity cross-section diagram of the crack inversion with h=0.5m is shown as follows Figure 7 shown.

[0086] S2. Measure the parameters of the cracks on the slope

[0087] Electrode rods 1 are arranged on the slope surface with a length and width of 2m each. Each adjacent four electrode rods 1 constitute a test area. Then, according to the maximum depth h of the crack determined in step S1, the electrode rods 1 are inserted into the slope body to a depth of h = 0.5m. The electrode 2 on the electrode rod 1 is moved to the same height as the slope surface, so that the electrode 2 contacts and fixes the probe at that location. The cable 3 on the electrode rod 1 is connected to the multi-channel electrode conversion device 5. After power is turned on, the apparent resistivity cross-section diagram in each test area is obtained. The test results of all test areas are combined together to obtain the apparent resistivity cross-section diagram of the slope surface section as shown in FIG. Figure 8 As shown by Figure 8 The number of cracks in the slope section is 5. Combined with the crack area parameters in each test area, the slope crack rate is:

[0088]

[0089] Where: s is the slope crack rate, A i is the crack area in the i-th test area, j is the number of test areas, and A is the area of ​​the entire test area. Substituting the data into the calculation, the slope crack rate is 5.13%.

[0090] S3. Measure the crack parameters of each layer and the crack rate of the entire area

[0091] After the slope crack parameter test is completed, the electrode 2 is moved down 0.1m each time and fixed in contact with the probe set on the electrode rod 1. After power is turned on, the number of cracks at the section with a depth of integer multiples of 0.1m, the length, width and crack area of ​​each crack can be measured. The measured crack parameters of each layer are matched with their depth and imported into the computer. The three-dimensional spatial form of the crack is calculated through the modeling software, and finally the volume crack rate of the entire test area can be obtained. The expression of the volume crack rate is:

[0092]

[0093] Where: v is the volume crack ratio, V i is the volume of the i-th crack, k is the number of cracks, A is the area of ​​the entire test area, and H is the test depth. Substituting the data into the calculation, the slope crack rate is 1.27%.

[0094] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. In particular, for the system embodiment, since it is basically similar to the method embodiment, the description is relatively simple, and the relevant parts can be referred to the partial description of the method embodiment.

[0095] The above description is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention are included in the protection scope of the present invention.

Claims

1. An in-situ test system for slope crack parameters based on resistivity method, characterized in that: It comprises a high-density resistance method host (6) arranged on the surface, one end of the high-density resistance method host (6) is connected to an electric energy conversion device (7) via a cable (3), and the other end is connected to a multi-channel electrode conversion device (5); the other end of the electric energy conversion device (7) is connected to a small wind turbine generator set (8) via a cable (3); the multi-channel electrode conversion device (5) is connected to an electrode (2) on an electrode rod (1) via a cable (3) and a probe; An electrode rod (1), the electrode rod (1) being inserted into the slope to be measured, the electrode rod (1) comprising a plurality of probes; An electrode (2) for measuring voltage, wherein the electrode (2) is fixed on different probes to achieve measurement at different depths; The probe is specifically a movable conductive probe, which is used to adjust the measurement depth and realize conduction between the electrode (2) and the multi-channel electrode conversion device (5).

2. A method for in-situ testing of slope crack parameters based on resistivity method, based on the in-situ testing system for slope crack parameters based on resistivity method as claimed in claim 1; characterized in that: The following steps are involved: S1. Select three most developed cracks on the slope through field survey and inject conductive hydrogel into these cracks; S2, determine the total length L of the three cracks measured by S1, the electrode rod spacing X, the isolation coefficient n and calculate the detection depth D = nX; S3, according to the data determined in S2, the electrode rods (1) are arranged at a spacing X, and the electrode rods (1) are connected via cables (3) to construct an electrode network in a vertical direction, and the electrode network is then connected in series with the cables (3) via a multi-channel electrode conversion device (5) to connect to a high-density resistance method host (6), so that the high-density resistance method host (6) can collect data of each electrode rod (1); The electrode mesh is placed at the midpoint of the width direction on the horizontal plane of the crack; S4. Determine the electrode rod (1) used for power supply and the electrode rod (1) used for measurement during the measurement process, use the high-density resistance method host (6) to convert the voltage data collected by each electrode rod (1) into resistivity data, determine the apparent resistivity of each measuring point, and perform two-dimensional inversion calculation on the apparent resistivity to obtain a high-density resistance method apparent resistivity cross-sectional distribution map of the three cracks along the depth direction, and finally determine the depths h1, h2, and h3 of the three cracks, and use the maximum value of the three as the deepest crack depth developed on the slope to be measured, recorded as h max ; S5. Inject conductive hydrogel into all cracks on the slope until it is flush with the slope surface, divide the slope surface into multiple rectangles according to 1 / 10 to 1 / 5 of the length and width of the slope, insert electrode rods (1) at the corner points of the rectangles, redistribute the electrode rods (1), and take the insertion depth as h max ; Move the electrodes (2) on all electrode rods (1) to the probe at the same height as the slope surface and fix them to detect and measure the crack parameters on the slope surface; S6. Measure the crack parameters of each layer and the volume crack ratio of the slope.

3. The in-situ testing method for slope crack parameters based on resistivity method according to claim 2 is characterized in that: The spacing X between the electrode rods (1) in S2 is between 1 / 10 and 1 / 15L.

4. The in-situ testing method for slope crack parameters based on resistivity method according to claim 2 is characterized in that: The determination process of the apparent resistivity cross-section distribution map of the S4 high-density resistance method is as follows: S401, setting the spacing between the electrode rods (1) to X, selecting the first and fourth electrode rods (1) as power supply electrode rods A and B, and the second and third electrode rods (1) as measurement electrode rods M and N for measurement; marking the underground resistivity characteristic at the midpoint between the two points MN and the depth X as point a; S402, keeping the spacing between the electrode rods (1) at X, selecting the second and fifth electrode rods (1) as power supply electrode rods A and B, and the third and fourth electrode rods (1) as measurement electrode rods M and N for measurement; marking the underground resistivity characteristic at the midpoint between the two points MN and the depth X as point b; repeating the process of S401 to S402 until the measurement of all the measurement points in the row of line ab is completed; S403, setting the spacing between the electrode rods (1) to 2X, selecting the first and seventh electrode rods (1) as power supply electrode rods A and B, and the third and fifth electrode rods (1) as measurement electrode rods M and N for measurement; marking the underground resistivity characteristic at the midpoint between the two points MN and the depth of 2X as point c; repeating the process of S403 until the measurement of all measurement points in the row of point c is completed; S404, the spacing between the electrode rods (1) is set to 3X and 4X, and measurements are performed respectively according to the method of S403, and the measured data are processed by the high-density resistance method host (6) and modeled as an apparent resistivity diagram of the cross section.

5. The in-situ testing method for slope crack parameters based on resistivity method according to claim 2 is characterized in that: The process of detecting crack parameters of the slope surface section by S5 is specifically as follows: the electrode (2) is moved to the probe located on the slope surface of the electrode rod (1), and all cables (3) connected to the electrode rod are connected to the multi-channel electrode conversion device (5); after measuring each rectangular test area, the data is processed by the high-density resistance method host (6) to determine the apparent resistivity cross-sectional diagram of the slope surface section, and the number of cracks in the slope surface section, the length, width and area of ​​each crack and the specific position of the crack on the section are determined by the output result of the host, thereby determining the slope surface crack rate.

6. The in-situ testing method for slope crack parameters based on resistivity method according to claim 2 is characterized in that: The specific method for determining the slope surface crack rate is: Where: s is the slope crack rate, A i is the crack area in the i-th test area, j is the number of test areas, and A is the area of ​​the entire test area.

7. The in-situ test method for slope crack parameters based on resistivity method according to claim 2 is characterized in that: In the S5, four electrode rods (1) are arranged in a group to form a rectangular test area, wherein the current input ends are electrode rods A and B; and the measuring electrode rods are M and N.

8. The in-situ test method for slope crack parameters based on resistivity method according to claim 2 is characterized in that: The specific process of S6 is as follows: the electrode rod (1) is evenly divided into m sections, the length of each section is x, probes are set at both ends of each section, the electrode (2) is fixed on the probe at a distance x from the slope surface, and the cable (3) is connected to the multi-channel electrode conversion device (5) to start measurement; when the measurement of the depth of the slope surface is x layers, the electrode (2) is moved downward to the next probe and the measurement is repeated until the depth is h. max obtain the crack parameters at the section with a depth that is an integer multiple of x, establish a three-dimensional spatial model with the crack parameters, and determine the volume crack rate of the entire slope based on the three-dimensional spatial model.

9. The in-situ test method for slope crack parameters based on resistivity method according to claim 7, characterized in that: The method for determining the volume crack rate is specifically as follows: Where: v is the volume crack ratio, V i is the volume of the i-th crack, k is the number of cracks, A is the area of ​​the entire test area, and H is the test depth.

10. The in-situ test method for slope crack parameters based on resistivity method according to claim 2, characterized in that: The specific components of the hydrogel include: 10 to 12 parts by mass of agarose powder, 0.5 to 1.5 parts by mass of carbon nanotubes, and 18 to 20 parts by mass of sodium chloride; The hydrogel is specifically prepared by the following method: firstly, sodium chloride powder is dissolved in deionized water with a mass fraction of 90 to 110 to prepare a sodium chloride solution, and then agarose powder and carbon nanotubes are mixed and stirred to obtain a mixed powder, and after stirring evenly, the prepared sodium chloride solution is slowly added to the mixed powder.

Citation Information

Patent Citations

  • Method for preventing seepage by glue injection to side wall of irregular undisturbed fractured rock

    CN105928764A

  • Multi-dimensional detection apparatus and method of exploring riverway karst cave

    CN107045147A

  • Expansive soil three-dimensional fracture spatio-temporal evolution model test system

    CN116577483A

  • Multi-energy complementary energy storage system and method based on power grid

    CN117996803A

  • Alternation of wetting and drying crack measuring device of indoor soil property side slope model

    CN204832095U